RELATIONSHIP BETWEEN MATERNAL AND CHILD OVERWEIGHT - Cunha, Madalena (2013)
Introduction: It is recognized that overweight in childhood as a multifactorial etiology, and parent’s obesity, particularly mother’s obesity is actually known to be an important predictor of the development of obesity in their children. Objectives: To classify the children’s and the mother’s BMI and assess the relationship between maternal and child overweight. Methods: Cross-sectional and observational study comprising 1424 preschool children, average age 4.58 years old (SD=0.990) and their mothers, average aged 34.46 years (SD= 5.29), living in centre/north of Portugal, 56.9% in rural area and 49.5% with their parents and siblings. The anthropometric evaluation and children’s classification was based on the referential NCHS (CDC, 2000) and WHO (2001) reference for the mothers. Results: In the sample 60.0% had normal weight, 38.2% were overweight (including 17.5% obesity) and 1.8% low-weight, but the differences shown to be independent from age and gender of children. In the mothers, 42.3% showed overweight, included 12.3% obesity. The probability of the child being overweight is 1.5 higher, when the mother has overweight (OR= 1.573; IC 95%= 1.229–2.012) and near twice higher, in mother/daughter relationship (OR= 1.946; IC 95%= 1.362–2.782). Conclusion: Like in other studies, the inferences revealed that there was significant effect of BMI of mothers in the development of children's overweight, particularly in girls, so that, the prevention of children’s obesity should consider health education aimed to the whole family, focused in the mother-daughter dyad, in order to be more effective in the interventions to the child.